Business Platforms for Fostering Entrepreneurship Among People with Disabilities: Advancing SDG 8 and SDG 10 - Mutya Paramita Pratitab; Naili Amalia; Marjam Desma Rahadhini (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2026)
Objective: To analyze the role of business in encouraging entrepreneurship and independence for people with disabilities and to identify the factors that support their participation in the labor market. Method: Employing a literature observation method by collecting data from journals, books, and internet sources, which were analyzed using descriptive techniques. Case studies were also conducted on workers with disabilities in three businesses in Surakarta City: Coffeeshop SKA eRCe, Gudang Alfamart, and Matahari Department Store. Results: The findings indicate that formal education and basic IT skills facilitate the entry of people with disabilities into the job market. Institutional and social service support plays a significant role in providing recommendations and job placement. In addition, companies committed to inclusion and empowerment of people with disabilities experience improved performance and increased revenue. Novelty: Demonstrating the role of business as an effective platform for fostering entrepreneurship and economic independence among people with disabilities. By highlighting the mutual benefits of disability inclusion for both employees and organizations including improved well-being, economic contribution, organizational performance, and business reputation the study provides empirical evidence supporting SDG 8 (Decent Work and Economic Growth) through inclusive employment and entrepreneurship, as well as SDG 10 (Reduced Inequalities) by promoting equitable participation in economic activities.